2013
DOI: 10.1080/1533256x.2012.756341
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Trauma-Informed Systems Change in a Family Drug Treatment Court Context

Abstract: Abstract:A growing body of literature documents the importance of trauma-informed and trauma-specific services and systems change in both addiction treatment and child welfare fields. The overall aim of this qualitative study was to explore barriers, benefits, and facilitating factors associated with a trauma-informed systems assessment and improvement initiative conducted in the context of a family drug treatment court (FDTC). Semi-structured in-depth interviews with 12 key informants and historical analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…Organizational change literature demonstrates that innovation is nearly impossible when an organization is confronted with so many threats to its basic existence. When this is the case, all attention goes toward basic survival of the organization (Drabble, Jones, & Brown, 2013). Unfortunately, given the prevalence of these conditions for such programs, administrative enthusiasm for the project, which had been strong at the start of the research project, declined considerably over time.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational change literature demonstrates that innovation is nearly impossible when an organization is confronted with so many threats to its basic existence. When this is the case, all attention goes toward basic survival of the organization (Drabble, Jones, & Brown, 2013). Unfortunately, given the prevalence of these conditions for such programs, administrative enthusiasm for the project, which had been strong at the start of the research project, declined considerably over time.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent qualitative study (Drabble, Jones & Brown 2013), staff members and administrators from a variety of agencies involved in a California county's Family Drug Court Collaborative reported that the Trauma-Informed Assessment: (1) heightened their awareness of what parents have to go through and how that impacts their children;…”
Section: The Assessment Processmentioning
confidence: 99%
“…Data can be analyzed and time set aside to study results, compare data to the team's predictions, and reflect upon what was learned . Process evaluations may examine the extent to which program delivery staff and other school staff report increased understanding of trauma and its impact on health, heightened awareness of the traumatic experiences of students, increased sensitivity and respect for students, self‐examination of how staff inadvertently contribute to re‐traumatizing students, and understanding of what it means to be trauma‐informed . Outcome evaluation might seek to answer questions such as: (1) Compared to program delivery as usual, does trauma‐informed program delivery result in better outcomes as measured by student engagement, decreased risk behavior, and decreased adolescent pregnancy?…”
Section: Implications For School Healthmentioning
confidence: 99%